2014
DOI: 10.1007/s10620-014-3142-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Management of Patients with Chronic Hepatitis B in an Integrated Care Setting

Abstract: Background Few population-based studies have described characteristics and management of patients with chronic hepatitis B (CHB) in the USA. Methods We retrospectively studied adults with CHB in the Northern California Kaiser Permanente Medical Care Program (KPNC) from July 2009 to December 2010 (n = 12,016). Laboratory tests, treatment patterns, and hepatocellular carcinoma (HCC) surveillance were ascertained during a “recent” 18-month study window (July 2009–December 2010), or as “ever” based on records da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Similar to previous studies, we found low adherence to recommended laboratory testing and significant gaps in the clinical recognition of HBV diagnosis and subsequent follow-up care. (8)(9)(10)(11) A minority of patients had the HBV diagnosis code entered into the medical record by providers, and fewer than half had confirmatory testing 6 months after the initial HBsAg result. Although patients with confirmed chronic HBV infection had higher rates of recommended laboratory testing, testing rates were still suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to previous studies, we found low adherence to recommended laboratory testing and significant gaps in the clinical recognition of HBV diagnosis and subsequent follow-up care. (8)(9)(10)(11) A minority of patients had the HBV diagnosis code entered into the medical record by providers, and fewer than half had confirmatory testing 6 months after the initial HBsAg result. Although patients with confirmed chronic HBV infection had higher rates of recommended laboratory testing, testing rates were still suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with recently published studies that have found rates of antiviral initiation ranging from 14% to 72%. (8,9,28,29) Although increased rates of HBV DNA testing and receipt of specialty care were noted following the most recent 2009 AASLD guidelines, rates of appropriate confirmatory testing dropped slightly and rates of antiviral therapy initiation remained stable at about 40%, suggesting that guidelines do not necessarily result in changes in clinical practice. The findings that treatment with antiviral therapy and one-time liver imaging were independently associated with lower all-cause mortality need to be prospectively confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, fewer than half of the estimated 2 million cases of hepatitis B have been diagnosed and only a fraction of those infected are being adequately managed. 1,2 The study by Mukhtar and colleagues highlights some of the barriers to hepatitis B screening. 3 Not surprisingly, testing rates for hepatitis B were positively associated with provider attitudes and negatively associated with providers' perceived barriers to testing.…”
mentioning
confidence: 99%